Legal Skills - Emily Finch, Stefan Fafinski (United Kingdom Oxford University Press, 2021)
'Legal Skills' encompasses all the academic and practical legal skills vital to a law degree in one manageable volume. It is an ideal text for the first year law student and a valuable resource for those studying law at any level.
Keywords: Law; (UGB110) Business Law